2021
DOI: 10.3389/fcvm.2021.671198
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Cardiovascular Risk Factors After Kawasaki Disease

Abstract: First described in Japan 50 years ago, Kawasaki disease is a worldwide multisystem disease. It is an acute self-limited vasculitis of unknown etiology that can lead to coronary artery lesions, such as dilatation, aneurysms, and stenosis in children. It is one of the common causes of acquired heart disease among children in developed countries. The coronary aneurysm is a severe complication in the acute stage, possibly leading to stenotic lesions or myocardial ischemia. More concerns have centered on endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 77 publications
0
22
0
Order By: Relevance
“…Most of the patients in the study group had abnormalities in the lipid profile, most often in the form of high triglyceride levels and low high-density lipoprotein (HDL) levels ( 22 ). It is worth emphasizing that among the ionic disturbances in children with PIMS, there are also visible disturbances in vitamin D3 concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the patients in the study group had abnormalities in the lipid profile, most often in the form of high triglyceride levels and low high-density lipoprotein (HDL) levels ( 22 ). It is worth emphasizing that among the ionic disturbances in children with PIMS, there are also visible disturbances in vitamin D3 concentration.…”
Section: Discussionmentioning
confidence: 99%
“…The role of vitamin D3 as a protective factor for the circulatory system has been emphasized in the literature for many years. The long-term effects of low vitamin D3 levels and the abnormalities in the lipid profile found in PIMS-TS syndrome may predispose to the earlier development of atherosclerosis or heart failure in these patients ( 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of these patients, 150,000 were over 20 years of age, and 15,000 were over 40 years (from 1964 to 31 December 2016) [ 2 , 3 ]. Among adult patients with KD, it has been reported that vasculitis might induce the early progression of atherosclerosis [ 4 , 5 , 6 ]. The pathological image of chronic KD cardiovascular sequelae is mainly composed of sclerotic lesions after vasculitis, which is pathologically different from usual atherosclerotic lesions [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among adult patients with KD, it has been reported that vasculitis might induce the early progression of atherosclerosis [ 4 , 5 , 6 ]. The pathological image of chronic KD cardiovascular sequelae is mainly composed of sclerotic lesions after vasculitis, which is pathologically different from usual atherosclerotic lesions [ 6 , 7 ]. However, it has been demonstrated that chronic vascular endothelial cell damage persists in patients with KD due to the tissue infiltration of inflammatory cells such as macrophage and activation of the immune system by releasing inflammatory cytokines [ 5 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation